Design and Methodology of the Study of Associated Risks of Stillbirth (SOARS) in Utah. (January 2022) - DeSisto, Carla L.; Stone, Nicole; Algarin, Barbara; Baksh, Laurie; Dieke, Ada; D'Angelo, Denise V.; Harrison, Leslie; Warner, Lee; Shulman, Holly B.
Objectives: The Utah Study of Associated Risks of Stillbirth (SOARS) collects data about stillbirths that are not included in medical records or on fetal death certificates. We describe the design, methods, and survey response rate from the first year of SOARS. Methods: The Utah Department of Health identified all Utah women who experienced a stillbirth from June 1, 2018, through May 31, 2019, via fetal death certificates and invited them to participate in SOARS. The research team based the study protocol on the Pregnancy Risk Assessment Monitoring System surveillance of women with live births and modified it to be sensitive to women's recent experience of a stillbirth. We used fetal death certificates to examine survey response rates overall and by maternal characteristics, gestational age of the fetus, and month in which the loss occurred. Results: Of 288 women invited to participate in the study, 167 (58.0%) completed the survey; 149 (89.2%) responded by mail and 18 (10.8%) by telephone. A higher proportion of women who were non-Hispanic White (vs other races/ethnicities), were married (vs unmarried), and had ≥high school education (vs <high school education) responded to the survey. Differences between responders and nonresponders by maternal age, gestational age of the fetus, or month of delivery were not significant. Among responders, item nonresponse rates were low (range, 0.6%-5.4%). The question about income (4.8%) and the questions about tests offered and performed during the hospital stay had the highest item nonresponse rates. Conclusions: The response rate suggests that a mail- and telephone-based survey can be successful in collecting self-reported information about risk factors for stillbirths not currently included in medical records or fetal death certificates.